Catechol-bearing block copolymer micelles: Structural characterization and antioxidant activity. (1st June 2015) - Hasegawa, Urara; Moriyama, Masaki; Uyama, Hiroshi; van der Vlies, André J.
Abstract: Oxidative stress caused by uncontrolled production of reactive oxygen species (ROS) has been linked to the initiation and progression of some diseases. Therefore, the use of antioxidants capable of scavenging ROS has attracted growing interest. We recently reported antioxidant micelles having catechol moieties, a structural motif found among natural antioxidants. These micelles showed a strong inhibitory effect in ROS-mediated angiogenesis as compared to the small catecholic compound dopamine. Here, we aim to explain this interesting function of the micelles by correlating the effects of self-assembled structures on the auto-oxidation stability and anti-angiogenic activity. The micelles were prepared from a hydrophilic poly( N -acryloyl morpholine) and a hydrophobic catechol-bearing block with different catechol content. The micelles with higher catechol content formed stable spherical micelles and showed increased stability against auto-oxidation, while micellization did not affect the redox potential of catechol moieties. Furthermore, the micelles with higher catechol content showed a stronger anti-angiogenic activity. Graphical abstract: Highlights: Preparation of catechol-bearing micelles with different catechol content. Increasing catechol content leads to more stable structures. The structural stability of the micelles affects the auto-oxidation of catechol. Micellization affects the kinetics but not thermodynamics of catechol oxidation. Micelles scavenge H2 O2 and inhibit endothelial cell tube formation.